Effects of donkey milk on UVB-induced skin barrier damage and melanin pigmentation: A network pharmacology and experimental validation study - Li, Anqi; He, Hailun; Chen, Yanjing; Liao, Feng; Tang, Jie; Li, Li; Fan, Yumei; Li, Li; Xiong, Lidan (Frontiers in Nutrition, 2023)
Introduction Dairy products have long been regarded as a controversial nutrient for the skin. However, a clear demonstration of donkey milk (DM) on skincare is required. Methods In this study, spectrum and chemical component analyses were applied to DM. Then, the effects of DM on UVB-induced skin barrier damage and melanin pigmentation were first evaluated in vitro and in vivo. Cell survival, animal models, and expression of filaggrin (FLG) were determined to confirm the effect of DM on UVB-induced skin barrier damage. Melanogenesis and tyrosinase (TYR) activity were assessed after UVB irradiation to clarify the effect of DM on whitening activities. Further, a network pharmacology method was applied to study the interaction between DM ingredients and UVB-induced skin injury. Meanwhile, an analysis of the melanogenesis molecular target network was developed and validated to predict the melanogenesis regulators in DM. Results DM was rich in cholesterols, fatty acids, vitamins and amino acids. The results of evaluation of whitening activities in vitro and in vivo indicated that DM had a potent inhibitory effect on melanin synthesis. The results of effects of DM on UVB‑induced skin barrier damage indicated that DM inhibited UVB-induced injury and restored skin barrier function via up-regulation expression of FLG (filaggrin). The pharmacological network of DM showed that DM regulated steroid biosynthesis and fatty acid metabolism in keratinocytes and 64 melanin targets which the main contributing role of DM might target melanogenesis, cell adhesion molecules (CAMs), and Tumor necrosis factor (TNF) pathway. Discussion These results highlight the potential use of DM as a promising agent for whitening and anti-photoaging applications.